Primera versión en español de la Escala de Fanatismo en el Deporte: Análisis psicométrico en adultos peruanos - Okumura Clark, Alvaro Jesús (2024)
Sports fanaticism is a non-highly studied concept, so instruments that evaluate this variable are relatively scarce. The current study aimed to obtain the psychometric properties of the first Spanish version of the Sports Fanaticism Scale (SFS) in Peruvian adults. 386 people participated (M=29.1 years, SD=12.1). Evidence of content validity was obtained through expert judgment (Vaverage =.84). The hierarchical model presented better fit indices for the EFD compared to a unidimensional model (RMSEA =.137; SRMR =.088; TLI =.939; CFI =.954). Convergent and divergent validity were determined through the association with relevant variables (r = -.296 -.446; AVE =.692 -.779; CR =.783 -.907). Acceptable internal consistency coefficients were obtained for general factor as dimensions (¿ =.67 -.92). EFD is an instrument that meets current psychometric standards. © Copyright 2018: Servicio de Publicaciones de la Universidad de Murcia Murcia (España) ISSN edición impresa:1578–8423 ISSNediciónweb(http://revistas.um.es/cpd):1989–5879